Killer immunoglobulin-like receptor and cancer - Jose María Gómez-Luque; Emilia Urrutia-Maldonado; Paloma Muñoz de Rueda; Ana Abril-Molina; Esther Ocete-Hita (Elsevier, 2022)
Introduction: Natural killer (NK) cells play an important role in defense against tumor cells. The development and function of NK cells is governed by a dynamic balance between inhibition and activation of cell surface receptors, including KIR receptors. Patients and method: A case-control study is carried out that compares a group of 46 children diagnosed with malignant diseases, the control group is made up of 82 healthy children. KIRs genes, haplotypes and ligands were determined and compared between groups. Results: There are no differences in KIRs genes, KIRs haplotypes or in KIRs gene ligands between groups. However, when KIRS and ligands were jointly studied, k2DS1_C2 was significantly higher in the group of cancer children (p = 0.016). Conclusions: Our results do not provide evidence of an association between pediatric cancer disease with genotypes and groups of genes KIRs. The k2DS1_C2 genotype could predispose to susceptibility to malignant processes in children. Resumen: Introducción: Las células natural killer (NK) juegan un papel importante en la defensa contra las células tumorales. El desarrollo y la función de las células NK se rige por un equilibrio dinámico entre la inhibición y la activación de los receptores de la superficie celular, incluidos los receptores KIR. Pacientes y método: Se realiza un estudio de casos y controles que compara a un grupo de 46 niños diagnosticados de enfermedades malignas, el grupo control está constituido por 82 niños sanos. Se determinaron y compararon entre grupos los genes, haplotipos y ligandos KIRs. Resultados: No existen diferencias en genes KIRs, haplotipos KIRs ni en ligandos de genes KIRs entre grupos. Sin embargo, al estudiar conjuntamente KIRs y ligandos, k2DS1_C2 fue significativamente superior en el grupo de niños oncológicos (p = 0,016). Conclusiones: Nuestros resultados no proporcionan evidencia de una asociación entre enfermedades oncológicas pediátricas con genotipos y grupos de genes KIRs. El genotipo k2DS1_C2 podría predisponer a la susceptibilidad a procesos malignos en la población infantil.